Exploration of the Specificity of Motor Skills Hypothesis in 7–8 Year Old Primary School Children: Exploring the Relationship Between 12 Different Motor Skills From Two Different Motor Competence Test Batteries - Sigmundsson, Hermundur; Newell, Karl M.; Polman, Remco; Haga, Monika (Frontiers in Psychology, 2021)
This study examined the specificity hypothesis by examining the association between two specific motor competence test batteries (Movement Assessment Battery for Children (MABC) and Test of Motor Competence (TMC)) in a sample of young children. In addition, we explored the factorial structure of the MABC and TMC. A total of 80 children participated in the study (38 girls and 42 boys) with a mean chronological age of 7.9 years (SD 0.55). The correlation between total score MABC and total z-score TMC was r = .46. In general, low pair-wise correlations (r2 < .20) between the different motor tasks were found. The highest correlation was between the placing bricks and building bricks r = .45 (TMC); the stork balance and jumping in squares r = .45 (MABC). These low pair-wise relations of items are consistent with findings from younger and older children’s age-related motor competence test batteries. Principal components analysis (PCA) showed that the 1st component accommodated 25% of the variance and was dominated in the top 5 variable weightings by items of the MABC test; whereas the 2nd component accommodated 12% of the variance with the higher weightings all from the TMC test. The findings provide evidence with children for specificity rather than generality in learning motor skills a viewpoint that has predominantly been driven by adult learning studies. The PCA revealed that the MABC and TMC are testing different properties of children’s motor competence though in both cases the variance accounted for is relatively modest, but generally higher than the motor item pair-wise correlation.